Study on general awareness regarding the problem of environmental degradation - Simona-Roxana Ulman (CES Working Papers, 2018)
In my paper, I particularly investigate the current level of awareness on the problem of environmental degradation. The analysis reveals some aspects that may be viewed as general conclusion at national level and may be useful for environmental policies in order to obtain higher results and to induce a correct behaviour practiced by part of the citizens and, consequently, more easily propagated among the Romanians. In addition, the paper discusses some of the main difficulties for integrating the environmental aspects within the theory and practices of economic development.
Keywords: 330; environmental degradation; general awareness regarding environment; economic perspectives on environmental degradation